UC special plate number sale reaches RM3 million, now open for public - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
KUANTAN, 24 February 2022 – Universiti Malaysia Pahang (UMP) recorded sales of the UC special registration number series reaching RM3 million since opening for bidding on 1 February 2022.